2023
DOI: 10.1111/jfd.13751
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological analysis of Nocardia seriolae isolated from a wide range of aquatic animals in Taiwan, based on their genotype and enzymatic activity

Abstract: Chronic disease following Nocardia seriolae infection in a wide range of aquatic animals has been reported in many Asian countries and recently in America and Mexico. This study aimed to investigate the epidemiological relationship among N. seriolae isolates in Taiwan by investigating their genotype and enzymatic activities. A total of 66 strains isolated from 14 known and four unknown host fish from five sites in Taiwan were characterized using five combined methods. High genotypic diversity was recognized am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…These networks ensure that the necessary virulence factors are produced and deployed by the organism during infection, regardless of genotypic variations. In our previous study, enzymatic activity (protease and aminopeptidase) was found to be strongly associated with these pulsotypes (Nguyen et al, 2023). These results indicate the possibility of genetic and enzymatic associations with N. seriolae virulence in orange‐spotted groupers.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…These networks ensure that the necessary virulence factors are produced and deployed by the organism during infection, regardless of genotypic variations. In our previous study, enzymatic activity (protease and aminopeptidase) was found to be strongly associated with these pulsotypes (Nguyen et al, 2023). These results indicate the possibility of genetic and enzymatic associations with N. seriolae virulence in orange‐spotted groupers.…”
Section: Discussionmentioning
confidence: 81%
“…Strain OT103003‐N11 (singleton A2), which was isolated in only one case of grey mullet Mugil cephalus in 2014, displayed noticeably low virulence in orange‐spotted grouper (40%). The unique genetic type of this isolate may be linked to its low virulence caused by low resistance to the host immune defences; this may explain why this strain is not well distributed among N. seriolae population from samples of 18‐year collection in our previous study (Nguyen et al, 2023). The original isolate OT105002‐AF15 (pulsotype A8) from grouper species was a predominant pulsotype in the PFGE analysis, causing repeatedly delayed mortality and long duration in both Trial 1 and 2.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations